Passive Franchise as an Innovation in the Development of Cooperative-Based Retail Networks - Wardhana, Tommy Andri; Hadna, Agus Heruanto; Darwin, Muhadjir; Hardi, Amirullah Setya (Interdisciplinary Social Studies, 2023)
Background: Franchising is a choice in developing a business network. One of the rampant franchise businesses in Indonesia is the development of retail store networks. Unfortunately, the presence of modern store-based retail stores is feared to threaten local businesses in the area such as the case in Kulon Progo. TOMIRA is seen as the best solution that mediates the interests of the private sector as retail owners, cooperatives, and local governments with the main goal of improving community welfare. Aim: This paper aims to reveal TOMIRA policy problems that occur and explore innovations in management strategies needed in the form of passive franchises. Method: Through a qualitative approach, this paper is able to present the results and policy problems of multi-actors, namely the government, private sector, cooperatives, and SMEs. Findings: Passive franchising is seen as a form of mitigation of policy problems in TOMIRA because it is able to provide a delegation system for cooperatives and the merger process with a temporary credit fund facilitating cooperatives while having an impact on increasing profits for both cooperatives and SMEs. The success of passive franchise implementation depends on the role and involvement of local governments, retail policies themselves, human resources, and management.